"My disability is part of me:" Disclosure and Students with Visible Disabilities - Tonette S. Rocco (Adult Education Research Conference, 2001)
Self-disclosure is "any information exchange that refers to the self, including personal states, dispositions, events in the past, and plans for the future" (Derlega & Grzelak, 1979, p. 152). An individual's disclosure creates comfort or discomfort in the person receiving the information in the disclosure (Chelune, 1979). The level of (dis)comfort created affects the response the receiver of the disclosure has. Disclosure can increase interpersonal intimacy and decrease interpersonal distance however it can produce the opposite effect, rejection (Wright, 1982). It is also assumed to be reciprocal in ordinary social relationships. The work done on disclosure and disability most often examines the effect disability has on the comfort level of able-bodied individuals (Elliott, MacNair, Herrick, Yoder & Byrne, 1991; Elliott, MacNair, Yoder & Byrne, 1991; Stephan, Stephan, Wenzel & Cornelius. 1991). Little research has been done on disability disclosure in education and employment. Learning is considered a major life activity under the Americans with Disabilities Act. The purpose of accommodation, under Section 504, is to provide students with disabilities an equal opportunity to achieve equal results (Biehl, 1978) with the intent of preventing exclusion based on disability status (Mangrum & Strichert, 1988). Accommodation is "an adjustment to the learning environment that does not compromise the essential elements of a course or curriculum" (Schuck & Kroeger, 1993, p. 63). In order to access the learning environment certain accommodations may be needed. The student discloses disability status, requests an accommodation, and the instructor complies with the request.